2007
DOI: 10.1021/ma702001h
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Depolymerization of Poly(olefin sulfone)s Possessing Photobase Generating Groups in the Side Chain

Abstract: A series of poly(olefin sulfone)s possessing photobase generating groups was synthesized, and photochemically induced depolymerization was investigated. The photobase generating groups used in this study produce primary or secondary amino groups by UV irradiation. The photochemically produced base extracts protons from the main chain of the poly(olefin sulfone) and induces a depolymerization reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…It has been reported that the depolymerization of poly(olefin sulfone)s is induced efficiently by secondary amines 12. Thus, a compound that generates a secondary amine was chosen as the PBG (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the depolymerization of poly(olefin sulfone)s is induced efficiently by secondary amines 12. Thus, a compound that generates a secondary amine was chosen as the PBG (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Photobase generators (PBGs) are neutral compounds that produce basic species when irradiated with light. Thus, when a film of a poly(olefin sulfone) is doped with a PBG, it exhibits depolymerization by photoirradiation 12, 13. In this study, the photoinduced depolymerization of poly(olefin sulfone)s comprised of volatile olefins was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The base generation mechanism is shown in Scheme 1. The photobase-generating group was designed to produce a secondary amino group because a secondary amino group can induce effective depolymerization of poly(olefin sulfone)s. 1 The polymers were synthesized according to Scheme 2.…”
Section: Samplesmentioning
confidence: 99%
“…Found: C, 64.66%; H, 7.65%; N, 6.23%. 1 H NMR (CDCl 3, 500 MHz) d 1.44 (m, 6H, ACH 2 A), 1.62-1.68 (m, 6H, ACH 2 A, CyAH), 1.85-1.90 (m, 2H, CyAH), 2.040 (q, 4H, ACH 2 A), 2.33 (t, 2H, ACH 2 A), 3.37 (s, 2H, CyAH), 3.75 (m, 2H, CyAH), 4.88 (m, 1H, CyAH), 4.98 (d, 2H, CH 2 @CHA), 5.05 (d, 2H, CH 2 @CHA), 5.52 (s, 2H, ArACH 2 AOA), 5.80 (m, 1H, CH 2 @CHA), 7.48 (t, 1H, ArAH), 7.55 (d, 1H, ArAH), 7.63 (t, 1H, ArAH), 8.06 (d, 1H, ArAH). 13 C NMR (DMSO, 500MHz) d 24.4 (ACH 2 ACH 2 ACOAOA), 28.2-28.6 (CH 2 @CHACH 2 ACH 2 ACH 2 ACH 2 ACH 2 ACH 2 ACH 2 A, ACH 2 ACH 2 ANA of Cy), 33.1 (CH 2 @CHACH 2 A), 33.7 (ACH 2 ACOAOA), 40.8 (ACH 2 ANA of Cy), 63.2 (AOACH 2 AAr), 68.7 (AOACHA (CH 2 ) 2 A), 114.5 (CH 2 @CHA), 124.6 (ACHA (Ar)), 129.1 (ACHA of Ar), 132.0 (ACA (Ar)), 133.9 (ACHA of Ar), 138.7 (CH 2 @CHA), 147.4 (ACHA (Ar)), 153.8 (NACOAOA), 172.2 (ACH 2 ACOAOA) IR (KBr) 1237 (s, asymm COAO str), 1333 (s, symm NAO str), 1528 (s, asymm NAO str), 1697 (s, C@O str), 2922 (s, CAH str).…”
Section: Journal Of Polymer Sciencementioning
confidence: 99%
See 1 more Smart Citation